Uncertain Living: Challenges of Orphans in the Philippines - Vergara, John Mark; Angeles, Ladee Abigail; Pagkalinawan, Ashley Angel; Villafranca, Maurice (JPAIR Multidisciplinary Research, 2018)
Orphan studies are scarce internationally and locally. However, the implications of these orphans are tantamount to the society’s effort to advancement. One of the problems that the Philippines need to address is its status on the abandoned, neglected and orphaned children. The country has an abandoned children problem (Kaiman & De Leon, 2016). About 1.8 million children in the Philippines are under the status of abandoned or neglected. This phenomenological study focused on the experiences, aspirations, and fears of orphaned children living in and outside the orphanage. The study sought ethical clearance from the ethics committee to ensure that ethical standards were observed. Trustworthiness and rigor were ensured through member checking. Measures to protect participants’ confidentiality and anonymity were followed. Five (5) participants were purposively chosen through criterion sampling and data were collected through semi-structured interview. Narratives were transcribed verbatim and reflectively analyzed using Collaizi’s (1978) Procedural Steps. Analyzed narratives revealed three (3) dominant themes: (1) Nay, Tay, Bakit? Questions of Sufferings, (2) Paglaho ng Alaala: Standing Anchored in the Ground (3) Bakas ng Nakalipas: A Choice to Move Forward. The study revealed that the orphans underwent social, emotional, mental, spiritual and physical difficulties as an orphaned child. The study includes suggestions and recommendations for exploring the health and nutritional status and psychological well-being of an orphan.